ПЕДАГОГІЧНІ УМОВИ РОЗВИТКУ КРЕАТИВНОСТІ СТУДЕНТА В ПРАКТИЦІ РОБОТИ ВИЩОЇ ШКОЛИ (Педагогіка вищої та середньої школи, 2007)
The problem of future teacher's creativity of higher pedagogical institutions of education is being researched in the work. The subject, creativity structural components, pedagogical of future teacher’s are described.